Risk factors for disease severity, unimprovement, and mortality in COVID-19 patients in Wuhan, China. (June 2020) - Zhang, J.; Wang, X.; Jia, X.; Li, J.; Hu, K.; Chen, G.; Wei, J.; Gong, Z.; Zhou, C.; Yu, H.; Yu, M.; Lei, H.; et al.
Abstract: Objective: In December 2019, coronavirus disease (COVID-19) emerged in Wuhan. However, the characteristics and risk factors associated with disease severity, unimprovement and mortality are unclear and our objective is to throw some light on these. Methods: All consecutive patients diagnosed with COVID-19 admitted to the Renmin Hospital of Wuhan University from January 11 to February 6, 2020, were enrolled in this retrospective cohort study. Results: A total of 663 COVID-19 patients were included in this study. Among these, 247 (37.3%) had at least one kind of chronic disease; 0.5% of the patients ( n  = 3) were diagnosed with mild COVID-19, while 37.8% (251/663), 47.5% (315/663), and 14.2% (94/663) were in moderate, severe, and critical conditions, respectively. In our hospital, during follow-up 251 of 663 patients (37.9%) improved and 25 patients died, a mortality rate of 3.77%. Older patients (>60 years old) and those with chronic diseases were prone to have a severe to critical COVID-19 condition, to show unimprovement, and to die (p <0.001, <0.001). Multivariate logistic regression analysis identified being male (OR = 0.486, 95%CI 0.311–0.758; p 0.001), having a severe COVID-19 condition (OR = 0.129, 95%CI 0.082–0.201; p <0.001), expectoration (OR = 1.796, 95%CI 1.062–3.036; p 0.029), muscle ache (OR = 0.309, 95%CI 0.153–0.626; p 0.001), and decreased albumin (OR = 1.929, 95%CI 1.199–3.104; p 0.007) as being associated with unimprovement in COVID-19 patients. Conclusion: Male sex, a severe COVID-19 condition, expectoration, muscle ache, and decreased albumin were independent risk factors which influence the improvement of COVID-19 patients.